2021
DOI: 10.1038/s41378-021-00239-0
|View full text |Cite
|
Sign up to set email alerts
|

Spray-coated electret materials with enhanced stability in a harsh environment for an MEMS energy harvesting device

Abstract: The charge stability of electret materials can directly affect the performance of electret-based devices such as electrostatic energy harvesters. In this paper, a spray-coating method is developed to deposit an electret layer with enhanced charge stability. The long-term stability of a spray-coated electret is investigated for 500 days and shows more stable performance than a spin-coated layer. A second-order linear model that includes both the surface charge and space charge is proposed to analyze the charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 55 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The overall charge decay can be explained in terms of the quick decay of the surface charge in addition to the relatively slow decay of the space charge. 82 Furthermore, if the surface charges are captured by deep traps, space charges will decay much slower. 83 The enhancement of charge retention characteristics without the material's modification of MoS 2 in the time-dependent charge density measurement suggests the possible formation of space charges by introducing SiO 2 NPs between MoS 2 and Ni.…”
Section: Papermentioning
confidence: 99%
“…The overall charge decay can be explained in terms of the quick decay of the surface charge in addition to the relatively slow decay of the space charge. 82 Furthermore, if the surface charges are captured by deep traps, space charges will decay much slower. 83 The enhancement of charge retention characteristics without the material's modification of MoS 2 in the time-dependent charge density measurement suggests the possible formation of space charges by introducing SiO 2 NPs between MoS 2 and Ni.…”
Section: Papermentioning
confidence: 99%
“…It can be easily incorporated into systems without using any large storage space. [45][46][47][48][49][50][51][52] Bourouina et al, in Figure 4a, reported a silicon-based MEMS electrostatic transducer for vibration energy harvesting to obtain a functional device using electret materials in microsystems. [45] They demonstrated that 61 nW was obtained at a 0.25 g vibration level at 250 Hz.…”
Section: Mems-based Devicesmentioning
confidence: 99%
“…They demonstrated that the spray‐coated cyclic olefin copolymer can be well used in MEMS electret with ≈11.72 W power output at an acceleration of 28.5 m s −2 . [ 52 ] Herein, Table 2 concludes the key parameters of the MEMS‐based electret device for energy harvesting.…”
Section: From Energy Harvesting To Its Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…For the homocharge electret polymer films which are often utilized in electrostatic energy harvesters, the typical value of the effective surface charge density ranges from 0.1 to 1 mC/m 2 . The electrostatic energy harvesters embedded with electrets have captured much attention given their features such as self-powered capability (no bias voltage required), compatibility with MEMS processes, high conversion efficiency, simple implementation and eco-friendliness [21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%